HOW BLOOMBERG PRESSURES EDITORS. - Kadlec, Daniel (Columbia Journalism Review)
Presents how Bloomberg, computer terminals that provide business and financial information, pressures newspaper editors. Revenues of the media company founded by Michael Bloomberg in 1981; Information about the company; Terminals as its main business; How the cases were resolved.